(untitled) (Annals of Medical Research, 2023)
Aim: The aim of this study is to group patients with plantar heel pain and calcaneal spurs detected via lateral foot x-rays based on the angle between the spur and the calcaneus and compare the efficacy of an Extracorporeal shock wave therapy (ESWT) treatment between these groups. Materials and Methods: The patients were divided into three groups based on the measurement the angle between the plantar calcaneal spur and the calcaneus. Those with a measured angle of <30° were classified as Group 1, ranging between 30–60° as Group 2, and >60° as Group 3. Demographic characteristics, spur length, visual analog scale (VAS) and foot function index score (FFI), and pain and function evaluation were used as the pre-and posttreatment data in each group. Results: Out of the 170 patients, 96 (56.5%) were included in Group 1, 65 (38.2%) were in Group 2, and 9 (5.3%) in Group 3. The posttreatment VAS and FFI scores of the patients were significantly lower than the pretreatment scores (p<0.001). It was determined that the highest and lowest VAS and FFI score changes in the posttreatment period was in Group 3 and Group 1, respectively. In the correlation analysis, a positive correlation was found between the measured angle value and pretreatment VAS and FFI scores, age, and spur length. Conclusion: ESWT is an effective treatment method for calcaneal spurs, but further studies are needed on PCS classifications and the efficacy of the treatment selected based on these classifications.